Advertising Innovation across social networks - a study of foreign and national ads - - WADAH, FOUAZ (Milev Journal of Research and Studies, 2016)
This study dealt with one of the most important topics of marketing, namely advertising innovation through social networks, on the grounds that this method of advertising is important for innovative institutions that seek to introduce its products and services, and access to the largest domestic and international market segments, relying on various means of communication especially those related to modern technology, and given access to larger market segments through social networks which are attracting millions of users, most institutions have considered its use to advertise catalog in accordance with the technological innovative ways, we have dealt in our paper with the induction of the reality of the marketing advertising for some institutions, to reach at the end to the conclusion that access to a significant market sectors through this kind of advertising, in addition to the benefit from the cost savings compared to the traditional advertising style.